National Survey of Pharmacy Practice at MOH Hospitals in Saudi Arabia 2016-2017: Pharmacy Inventory Control and Stock Management - Alomi, Yousef Ahmed; Alghamdi, Saeed Jamaan; Alattyh, Radi Abdullah (Journal of Pharmacy Practice and Community Medicine)
Objectives: To explore the pharmacy inventory control and stock management at Ministry of Health (MOH) hospitals in Saudi Arabia. Methods: It is a 4-months cross-sectional National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia. The study consisted of two parts; the demographic information and the second part contained eighty-five questions divided into eight domains drove from American Society of Health-System Pharmacists (ASHP) and Saudi Pharmaceutical Society (SPS) survey, the international standard of Joint Commission of Hospital Accreditation in addition to the local standards of Saudi Center of healthcare accreditation. The parts were pharmacy management and resources, prescribing and medication control, preparation of medications and dispensing, Computerized and pharmacy technology, clinical pharmacy services, drug monitoring and patient’s education, Pharmacy inventory control and stock management, Pharmacy education and training, pharmacy total quality management and drug information services. The 5-point Likert response scale system with closed and ended questions were used. An electronic questionnaire was distributed to the one hundred eighty-five directors of pharmacies at MOH hospitals. The study discussed and analyzed National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia: pharmacy inventory control and stock management. Results: The survey questionnaire distributed to 185 hospitals, the rate of reply was 105 (56.75%) hospitals. The inventory control system was founded at 3.58 (71.6%) hospital pharmacies with highest located at hospital more than 600 beds and 200-299 bed size. The separate medication store was founded in 3.52 (70.4%) of hospital pharmacies with highest located at hospital 200-299 bed size. The complete computerized inventory management system founded at 20 (19%) hospital pharmacies while 53 (50.5%) there is computerized inventory management system. The average score of stock management system was 2.9 (57.92%) with the highest element was a policy and procedure on short expired medication items 3.85 (77.03%) while lowest elements was a Bar-coding system for inventory management system 1.54 (30.89%). The average score of follow-up report of stock management System was 3.22 (64.4%) with the highest report was Short Expired Items Report 3.8 (76%), and the lowest report was Reorder Point Report 2.72 (54.4%). The average score Stock Management System Medication availabilities were 1.83 (36.6%). The drug supply received from actual needing was 2.67 (53.4%), the medications borrowed from another hospital if it is not available in the pharmacy was 1.44 (28.8%) while the medications direct purchased to the hospital if it is not available in the pharmacy was 1.39 (27.8%). Conclusion: In hospital pharmacies, there was poor implementation of inventory management system. The full review of the drug stock management system with close monitoring is highly recommended to keep all medication available all the time, prevent under or overstock medications, and prevent all drug demand related problems.
Keywords: Pharmacy inventory control; Stock management; Ministry of health; Saudi arabia